How refugees in South Africa use mobile phones for social connectedness - Vuningoma, Sarah (Department of Information Systems, 2021)
Background: Refugees find it difficult to integrate and assimilate in their host country because of a myriad of challenges. Mobile phones have become one of the main tools for promoting their wellbeing and supporting the integration of refugee communities on the margins of society. Mobile phones can contribute towards reducing isolation and loneliness, and assist in improving interpersonal relations and fostering processes of assimilation. The purpose of the research: The main objective of this study was to examine how the use of mobile phones by refugees in South Africa contributes to their social connectedness. To this end, the study discusses the role of mobile phones in the process of acculturation, in creating a sense of belonging, and in maintaining relationships. Design/methodology/approach: This research employed a qualitative method and an interpretivist epistemological perspective. A conceptual framework was developed on the basis of a literature review. Data was collected from semi-structured interviews and WhatsApp group chats, and analysed using thematic analysis. The interviewees comprised 27 refugees living in South Africa, and the WhatsApp group had 15 members. Findings: The findings demonstrate that the refugees face a multitude of obstacles, including language and culture barriers, the challenge of obtaining legal status, physical separation from their friends and family, and feelings of being judged, insecure, and excluded. Mobile phone usage offers refugees several benefits, especially through their affordances that include accessing information, pursuing economic and institutional opportunities, enabling communication, and developing linguistic and cultural knowledge of the host country. At the same time, mobile phones enable refugees to maintain connection with their country of origin. Refugees nevertheless considered it difficult to develop a sense of belonging through their use of mobile phones. Research contribution: This study adds to perspectives on utilising mobile phones to achieve social connectedness for two categories of refugees: newcomers and old-timers. The study contributes to theory by proposing a framework for understanding and analysing the relationship between social connectedness and mobile phones. The study contributes to knowledge through the investigative approach of using WhatsApp group chat to collect data. The findings can contribute to enabling non-profit organisations and UNHCR to develop strategies and processes for providing interventions for refugees.